Alpha thalassaemia-mental retardation, X linked - Gibbons, R (2006)
X-linked alpha thalassaemia mental retardation (ATR-X) syndrome in males is associated with profound developmental delay, facial dysmorphism, genital abnormalities and alpha thalassaemia. Female carriers are usually physically and intellectually normal. So far, 168 patients have been reported. Language is usually very limited. Seizures occur in about one third of the cases. While many patients are affectionate with their caregivers, some exhibit autistic-like behaviour. Patients present with facial hypotonia and a characteristic mouth. Genital abnormalities are observed in 80% of children and range from undescended testes to ambiguous genitalia. Alpha-thalassaemia is not always present. This syndrome is X-linked recessive and results from mutations in the ATRX gene. This gene encodes the widely expressed ATRX protein. ATRX mutations cause diverse changes in the pattern of DNA methylation at heterochromatic loci but it is not yet known whether this is responsible for the clinical phenotype. The diagnosis can be established by detection of alpha thalassaemia, identification of ATRX gene mutations, ATRX protein studies and X-inactivation studies. Genetic counselling can be offered to families. Management is multidisciplinary: young children must be carefully monitored for gastro-oesophageal reflux as it may cause death. A number of individuals with ATR-X are fit and well in their 30s and 40s. © 2006 Gibbons; licensee BioMed Central Ltd.